Study on the typical dose for local diagnostic reference level (DRL) in cerebral angiography for femoral catheter insertion - Adnan, Fatin Najwa (2025)
Introduction: Cerebral angiography uses a catheter inserted through the femoral artery and guided by fluoroscopy to visualise brain blood vessels involving higher radiation exposure. This study aims to establish typical doses for local diagnostic reference levels (DRLs) for femoral catheter insertion in cerebral angiography to improve patient safety. Objectives: This study aims to analyse the dose distribution (PKA in Gy.cm² and Ka,r in mGy) with three indications and age groups. Then, establish the typical dose and compare the establish typical dose with international. Methodology: This retrospective study analysed 116 patients (aged 18–78) who underwent cerebral angiography at Hospital Pakar Universiti Sains Malaysia (HPUSM), Kelantan between January 2020 and December 2024. Data were collected using the SIEMENS AXIOM-Artis Zee biplane system and retrieved from the PACS USM. The statistical analysis was performed, and typical dose was established at median values of dose distributions. Results: The highest kerma-area product (PKA) was 954.08 Gy.cm² while the lowest was 26.50 Gy.cm². The typical PKA doses were 270.08, 229.30, and 251.92 Gy·cm² for aneurysm, brain arteriovenous malformation (AVM), and carotid-cavernous fistula (CCF), respectively. Corresponding Reference Point Air Kerma (Ka,r) doses were 1277.00, 1159.00, and 1611.00 mGy. These values exceeded national DRLs (81 Gy·cm², 389 mGy), likely due to more complex cases, longer fluoroscopy times, and equipment differences. Conclusion: Both PKA and Ka,r increase proportionally with kV, total mA, and total fluoroscopy time. Typical doses for local DRL vary based on different clinical indications. Overall, this study supports radiation protection efforts by promoting standardised, locally tailored dose limits to improve patient care in neurointerventional radiology.